Mapeamento geográfico da ocorrência de cepas de Bacillus thuringiensis no Triângulo Mineiro e sua caracterização molecular - Cunha, Walter Vieira da (1999)
The indiscriminate use of synthetic organic insecticides has led researchers to develop alternative strategies for the management of insect pests. Among these, microbial insect control stands out, which has suggested a more rational use for insecticide use in insect control. Of the agents used in microbial control, bacteria have stood out for several characteristics that favor their production and management. One of the most used bacteria in insect control is Bacillus thuríngiensis, which presents a diverse load of toxins, presenting high specificity among insect orders as well as within the order itself. The search for new strains with desirable characteristics such as greater coverage and high toxicity for insect pests, has led researchers to use the tools of Molecular Biology with the intention of streamlining this process. In this work, the presence of Bacillus thuríngiensis in the Triângulo Mineiro was verified by extracting soil samples, which presented 0 to 26% mortality in Spodoptera frugiperda (Lepidóptera: Noctídae). The PCR and RAPD techniques were then used for the molecular characterization of these collected strains, with the objective of separating them between the lepidoptera, coleoptera and diptera orders. This facilitates the stage of determining the degree of toxicity since, with this determination, you already have the orders of the target insects in which the strains can be tested. For the PCR technique, specific primers were used, designed from the conserved region of the gene responsible for encoding the crystal protein. These primers were not able to separate the selected strains from the Triângulo Mineiro region, identifying only the strains used as controls. Then, the RAPD analysis was carried out, where there was a high degree of variability between the samples. With 13 primers amplifying 189 polymorphic markers, a matrix was constructed with the genetic distances, calculated by the Percentage of Disagreement method. A dendrogram was set up by the unweighted method of grouping in pairs (UPGMA), where at the level of 29% it was possible to notice the separation into three groups, the first being formed by the strains closest to the standard strain specific for lepidopterans, a second formed by two strains collected in the regions of Indianópolis - MG and Araguari - MG and the third by the standard strains specific for dipterans.